Social and Contextual Constraints on Embodied Perception. (March 2017) - Schnall, Simone
A number of papers have challenged research on physiological and psychological influences on perception by claiming to show that such findings can be explained by nonperceptual factors such as demand characteristics. Relatedly, calls for separating perception from judgment have been issued. However, such efforts fail to consider key processes known to shape judgment processes: people's inability to report accurately on their judgments, conversational dynamics of experimental research contexts, and misattribution and discounting processes. Indeed, the fact that initially observed effects of embodied influences disappear is predicted by an extensive amount of literature on judgments studied within social psychology. Thus, findings from such studies suggest that the initially presumed underlying processes are at work—namely, functional considerations that are informative in the context of preparing the body for action. In this article, I provide suggestions on how to conduct research on perception within the social constraints of experimental contexts.